2009
DOI: 10.1183/09031936.00080209
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-induced lung disease: a systematic literature review

Abstract: The anti-CD20 antibody rituximab has been reported to induce a heterogeneous spectrum of lung disorders. The aim of the present study was to critically review data on the clinical presentations, causality assessments and management strategies of lung diseases possibly related to rituximab.A systematic literature review was performed on English-language reports in PubMed until September 2008.Cases of lung diseases ascribed to rituximab (n545) were identified, with three time-to-onset patterns. The most common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
127
2
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 51 publications
3
127
2
22
Order By: Relevance
“…Other presentations include diffused alveolar patterns (9%) and macronodules (3%) [2]. However, ILD with diffused pulmonary micronodules was found in our patient and was never reported.…”
contrasting
confidence: 38%
See 3 more Smart Citations
“…Other presentations include diffused alveolar patterns (9%) and macronodules (3%) [2]. However, ILD with diffused pulmonary micronodules was found in our patient and was never reported.…”
contrasting
confidence: 38%
“…Mechanisms leading to late-onset ILD remain unclear. A potential explanation may be the induction and release of cytokines following rituximab binding to CD20 + cells [2,4]. Because the patient was treated concomitantly with cytotoxic drugs, we recognise that it is difficult to completely rule out cytotoxic FIGURE 1 Chest computed tomography scan revealing diffused micronodules over bilateral lung field.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the incidence of rituximab-induced interstitial lung disease was estimated to be very rare by the manufacturer (<0.03 %), more recent studies reported an incidence of 3.5-11 % Iu et al 2008 ;Nieuwenhuizen et al 2008 ). The CT pattern most often described is (sub)acute OP followed by NSIP (Lioté et al 2010 ).…”
Section: Rituximabmentioning
confidence: 99%